THE CURRENT LANDSCAPE OF CHILD PROTECTION SERVICES IN SOUTH AFRICA: A SYSTEMATIC REVIEW - Strydom, Marianne; Schiller, Ulene; Orme, Julie (Social Work/Maatskaplike Werk, 2020)
Child protection services are seen as the largest field of social work service delivery in South Africa. Repeated warnings of the ‘crisis state’ of child protection services have gone unheeded. The aim of this article is to determine the current landscape of child protection service delivery and research within the South African context. The developmental social welfare approach was used as the epistemological framework for this systematic review. Findings indicated a significant emphasis on statutory services and a lack of resources for family preservation efforts. Appropriate costing models should be generated to specify critical needs and garner support from stakeholders.